The Effect of Elite Athletes' Club Environment Communication Levels on Sportsman Behavior - Karakuş, S.; Yavuz Eroğlu, Sultan; Aksak, C. (ResearchTrentz Academy Publishing Education Services, 2022)
The aim of this research is to determine whether the in-club communications of elite athletes in different sports can predict their sportsmanship behaviors. The study group of the research consists of 145 athletes (51.7% male, 48.3% female) randomly selected in athlete training centers and TOHM centers. The club media communication levels of the athletes were measured with the 3D (trainer-athlete, athlete-athlete and manager-athlete) Club Environment Communication Questionnaire. Sportsmanship Behaviors, on the other hand, were measured with the Multidimensional Sportsmanship Orientation Scale, which had 4 dimensions (compliance with social norms, respect for rules and management, commitment to responsibilities in sports and respect for the opponent). While analyzing the data, multiple linear regression analysis technique was used. In the results of the research, it is seen that there are positive (linear) relations between the Scores of the Club Environment Communication and Sportsmanship Orientation Subscales. In addition, it was seen that the communication between the coach and the athlete significantly predicted the dimensions of compliance with social norms and respect for the opponent, and the communication between the athlete and the athlete significantly predicted the sub-dimension of commitment to responsibilities. The result of the study reveals that as the scores obtained from each of the sub-dimensions of club environment communication increase, the scores obtained from each of the sub-dimensions of sportsmanship orientation increase reciprocally. © 2022 Wolters Kluwer Medknow Publications. All rights reserved.
Keywords: Club Environment; Communication; Sports; Sportsmanship; adult; article; athlete; controlled study; elite athlete; female; human; human experiment; male; manager; questionnaire; randomized controlled trial; responsibility; social norm